Pendugaan Upwelling di Perairan Selatan Pulau Jawa Menggunakan Citra Satelit Aqua MODIS Perekaman Tahun 2014 - 2016 - Anom, Taufik Ali YSH; , Drs. Munawar Cholil, M.Si; , Dra. Alif Noor Anna, M.Si (2017)
Oceanography state waters south of Java is strongly influenced by the state of the monsoon system. When western monsoon (December to February) lasts usually occurs downwelling in the waters south of Java, while the east monsoon (June to August) takes place upwelling occurs in the waters south of Java. While in the transitional seasons occur a time of change or transition winds and currents that cause the changing pattern of sea surface temperature and chlorophyll-a. The pattern of the surface oceanographic dynamics such as sea surface temperature, chlorophyll-a, geostrophic currents, the wind and sea levels need to be studied further to the effectiveness of fisheries resources. The existence of the strong El Nino in 2015 caused the pattern of oceanic parameters changed quite drastically. The existence of the strong El Nino in 2015 underlying this research. The purpose of this study as follows; 1) Determining the variability of sea surface temperature upwelling events, 2) Determining the variability of chlorophyll-a with upwelling events, and 3) Detect pattern distribute upwelling phenomenon along Java's southern waters during January 2014-November 2016. This study uses a multi-sensor satellite data such as sea surface temperature (MODIS), chlorophyll-a (MODIS), the wind (WindSat), Flow Geostrophic (ASCAT), and sea level (Modelling BPOL). The satellite data were processed using multi GIS software in order to be converted into the data format and the tiff shp. The results showed upwelling and downwelling zones in the waters south of Java. Genesis upwelling that occurs during the season there in the South east Bali and East Java and then extends to the coastal waters of the South West Java. Downwelling phenomenon when the western season lasts only found in South Bali Strait and East Java. The existence of the strong El Nino in 2015 caused the upwelling sufficient duration longer than in 2014 and 2016. The pattern of upwelling events that occur when the El-Nino (2015) starting from the month from May to November. Based on the results, it can be concluded that the process of upwelling is not only awakened by the wind, but allegedly due Flow Katulistiwa South closer to the waters south of Java while the downwelling generated by the wind, variations in climate El Nino affect the incidence of upwelling and downwelling especially in the waters south of Java.